التربية وسؤال القيم: مقاربة نقدية في ضوء نظرية القيم القرآنية لمحمد أركون: Education and the Question of Values: A Critical Approach in Light of the Qur’anic Values Theory by Muhammad Arkoun - El- Nazlawy, Hanan; Hassanein, Hassan Hanafi; Mahmoud, Youssef Sayed; Mansour, Ashraf Hassan Abdel Aziz (Unisia, 2022)
استهدف البحث الحالي التعرف إلى رؤية محمد أركون لمنظومة القيم الإسلامية باعتباره أحد أهم رموز التيار الحداثي المعاصر، وذلك عبر نظرية القيم القرآنية التي قدمها ضمن مشروعه الفكري الضخم "نقد العقل الإسلامي". ومحاولة إجراء مقاربة نقدية لنظم التربية على القيم في المجتمعات الإسلامية في ضوئها. وقد اتبع البحث المنهج الوصفي التحليلي والمنهج النقدي. وتوصل إلى أن نظرية القيم القرآنية تهدف إلى محاولة إبراز إمكانية إجراء استعادة نقدية للمحورية الأخلاقية القرآنية في ضوء المناهج الحديثة لعلوم الإنسان والمجتمع؛ عبر تفكيك الاعتقاد بأنه لا يُمكن نقد القيم ذات المرجعية القرآنية باعتبارها مرجعية لا تُناقش، ولا تُمس مُستخدمًا المنهج الجنيالوجي، والذي كشف من خلاله أن هذه القيم تشكلت وفقًا لقوالب ثقافية، ونظم فكرية محكومة بالفضاء العقلي القروسطي. كما أنها جاءت لتلبية أغراض سياسية- ايديولوجية، وأن الأصل في استنباط القيم القرآنية أربعة معايير هي أسماء الله الحسنى، الشهادة، الأمة، والقانون الديني. وأن كل معيار من المعايير الأربعة يُمكن أن ينتج عنه قيم متباينة بتباين أسس، ومرتكزات وأهداف عملية الاستنباط. وقد انتهى البحث إلى وضع تصور يُمكن من خلاله تطوير عملية التربية على القيم في ضوء ما كشفت عنه النظرية. Abstract The current research aimed to identify Muhammad Arkoun's vision of the Islamic value system as one of the most important symbols of the contemporary modernist trend. This was through the theory of Quranic Values presented within his huge intellectual project "Critique of the Islamic Mind". It was also an attempt to conduct a critical approach to the systems of education on values ​​in Islamic societies on its light. The research followed the descriptive analytical method, and the critical method. This study concluded that the Qur'anic Values ​​theory aims to highlight the possibility of conducting a critical restoration of the Qur'anic moral centrality in the light of modern approaches to human sciences and society. It aims so by dismantling the belief that it is not possible to criticize the values ​​that have a Quranic reference as a reference that is not discussed or touched using the Genealogical Method, through which it was revealed that these values ​​were formed according to cultural templates and intellectual systems governed by the medieval mental space. It also came to meet political-ideological purposes, and that the basis for deducing Quranic values ​​is four criteria: the names of God, martyrdom, the nation, and religious law. In addition, each of the four criteria can result in varying values ​​with varying foundations, pillars and objectives of the deduction process. The research ended with the development of a vision through which the process of values ​​education can be developed in the light of what the theory revealed.